P09.48 Residual contrast enhancement and residual 5-ALA fluorescence are independent negative surgical prognostic factors in GBM - Sage, W. (Neuro Oncol, 2017)
BACKGROUND: Intraoperative 5-ALA fluorescence-guided resection and local chemotherapy using carmustine wafers (Gliadel) are recent advances in the surgical management of glioblastoma (GBM) that have been independently shown to improve survival in clinical trials. The benefit of carmustine wafers has not been examined in combination with 5-ALA guided resection followed by a temozolomide-based chemotherapy protocol. Materials and Methods: Single centre retrospective cohort study of 260 patients who underwent 5-ALA resection of confirmed WHO Grade IV glioma between July 2009 and December 2014. Propensity score matched analysis was used to compare survival between groups whilst controlling for baseline characteristics. A cox proportional hazards regression was performed to identify variable predicting survival. Results: Carmustine wafers showed no significant survival benefit over 5-ALA resection alone on propensity-matched analysis (median survival 14.2 vs 12.9 months; HR 0.97 [0.68-1.26], p=0.836). There was a trend towards higher incidence of wound infection requiring revision surgery in those who received carmustine. Cox regression analysis indicated that residual enhancement (HR 1.66 [1.25-2.22], p <0.001) and residual fluorescence (HR 1.57 [1.17-2.10], p = 0.003) were independently associated with reduced survival. In a substantial proportion (40.1%) of patients the intraoperative and post-operative assessment of residual disease differed. Conclusions: Carmustine wafers do not appear to offer additional survival benefit over 5-ALA fluorescence guided resection of GBM. Both residual 5-ALA fluorescence and residual contrast enhancing tumour on post-operative MRI are independent negative prognostic factors following resection of GBM. Residual enhancement should be considered when stratifying GBM patients for drug trials.